Early dialysis in a neonate with intrauterine lisinopril exposure. Issue 2 (1st March 2003) - Filler, G; Wong, H; Condello, A S; Charbonneau, C; Sinclair, B; Kovesi, T; Hutchison, J
Abstract : In general, angiotensin converting enzyme (ACE) inhibitors should be discontinued in pregnancy, as they can induce an ACE fetopathy. For the treatment of the latter, early peritoneal dialysis is recommended for in utero exposure to captopril and enalapril, although the outcome is poor. Early peritoneal dialysis has not previously been reported for lisinopril induced multiorgan failure. A case is reported in which treatment was given on postnatal day 3. The patient recovered from oligoanuria to almost normal renal function, and heart, brain, and musculoskeletal injury was reversible. This is despite relatively poor clearance of the drug through peritoneal dialysis. Analysis of the pharmacokinetic data suggests that haemodialysis or haemofiltration would be more efficacious for removal of the drug, and these treatments should be performed if available.